Treatment of extensively drug-resistant tuberculosis in Tomsk, Russia: a retrospective cohort study - Keshavjee, Salmaan; Gelmanova, Irina Y; Farmer, Paul E; Mishustin, Sergey P; Strelis, Aivar K; Andreev, Yevgeny G; Pasechnikov, Alexander D; Atwood, Sidney; Mukherjee, Joia S; Rich, Michael L; Furin, Jennifer J; Nardell, Edward A; et al. (The Lancet (British edition), 2008)
Mycobacterium tuberculosis strains that cause untreatable drug-resistant disease are a threat worldwide. We describe the treatment, management, and outcomes of patients with extensively drug-resistant tuberculosis in Tomsk, Russia. We undertook a retrospective cohort study of 608 patients with multidrug resistant tuberculosis who had treatment in civilian or prison services, between Sept 10, 2000, and Nov 1, 2004, according to the treatment strategy recommended by WHO. Clinical characteristics, management practices, and treatment outcomes of patients with extensively drug-resistant (XDR) tuberculosis and non-extensively drug-resistant (non-XDR) tuberculosis are described. The main outcome was the frequency of poor and favourable outcomes at the end of treatment. Of 608 patients with multidrug resistant tuberculosis, 29 (4·8%) patients had baseline XDR tuberculosis. Treatment failure was more common in patients with XDR tuberculosis than in those with non-XDR tuberculosis (31% vs 8·5%, p=0·0008). 48·3% of patients with XDR tuberculosis and 66·7% of patients with non-XDR tuberculosis had treatment cure or completion (p=0·04). The frequency and management of adverse events did not differ between patients with XDR and non-XDR tuberculosis. The chronic features of tuberculosis in these patients suggest that extensively drug-resistant tuberculosis may be acquired through previous treatments that include second-line drugs. Aggressive management of this infectious disease is feasible and can prevent high mortality rates and further transmission of drug-resistant strains of Mycobacterium tuberculosis. Bill & Melinda Gates Foundation, Eli Lilly Foundation, The Open Society Institute, Frank Hatch Fellowships in Global Health Equity at the Brigham & Women's Hospital, Infectious Disease Society of America, the Heiser Foundation, the United States National Institutes of Health, and the John D and Catherine T MacArthur Foundation.